Conserved stress-responsive genes involved in the early development of Euterpe Edulis - Layra de Medeiros Cardozo; Francine Alves Nogueira de Almeida; Vinicius Sartori Fioresi; Guilherme Bravim Canal; Liana Hilda Golin Mengarda; Adésio Ferreira; Marcia Flores da Silva Ferreira (Scientific Reports)
Abstract The palm tree Euterpe edulis (juçara) plays a crucial ecological and socioeconomic role in the Atlantic Forest. Its wide distribution suggests the presence of adaptive mechanisms for tolerance to abiotic factors, particularly during early developmental stages, such as water availability and shading. This study aimed to identify conserved and differentially expressed genes (DEGs) involved in the early development of E. edulis, analyzing different tissues and two divergent plant matrices. Using eight RNA-Seq libraries, the strategy was to obtain the first transcriptome for the species through reference mapping against the Elaeis guineensis genome, with focus on conserved genes, followed by differential expression and functional annotation analyses. Among the 32,000 conserved genes identified, 1,133 were differentially expressed, with 11 showing differential expression in both tissues, 678 exclusively in leaves, and 444 in roots. Genes responsive to critical stress factors during early development were identified, revealing matrix-specific environmental adaptations, as well as genes associated with metabolism, light stimuli, and structural development. Leaf tissues exhibited the highest number of exclusive DEGs, indicating greater gene modulation in this tissue. The identification of conserved and highly expressed genes constitutes the first genomic insights for E. edulis, providing a foundation for studies aimed at its management, conservation, and genetic improvement for this non-model and endangered organism.